Pendekatan Kepolisian dalam Menanggulangi Kekerasan terhadap Anak di Era digital - Rabiah Al Adawiah (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2024)
The rapid development of technology and the internet has granted children in Indonesia broad access to information and communication, while simultaneously increasing the risk of child abuse. In addressing this issue effectively, the Indonesian National Police (Polri) plays a crucial role in developing a comprehensive approach to safeguard children in the digital era. Collaboration between Polri and relevant agencies, including the Ministry of Communication and Information Technology (Kominfo), the Ministry of Women Empowerment and Child Protection (Kemen PPPA), the Indonesian Child Protection Commission (KPAI), and the National Commission for Child Protection (Komnas PA), is essential in establishing a child protection ecosystem. Key elements in expediting case management and ensuring the safety of children in the digital realm include the monitoring of cybercrime, law enforcement, integrated reporting systems, strengthening legal frameworks, victim rehabilitation, and the training of law enforcement personnel. This research aims to analyze the Indonesian National Police's (Polri) approach to addressing child abuse in the digital era and to explore the challenges encountered in these efforts. The research questions posed in this study are: (1) What are the challenges faced in combating technology-based child abuse in the digital age? (2) How does Polri handle child abuse in the digital era? (3) How does Polri collaborate with other institutions in addressing child abuse? This research is a descriptive-prescriptive study. It uses secondary data, allowing the researcher to gain a broader perspective on the role of the police and its collaboration with other institutions in addressing child abuse.